Estudo da relação entre o acesso ao Portal de Periódicos da CAPES e a produção científica indexada nas bases Web of Science e Scopus das maiores universidades federais do Nordeste - Silva, Alessandra Meira da (2019)
This exploratory and descriptive study has as object the public postgraduate policies, focusing on the Portal of Periodicals of CAPES implemented by the Federal Government, which aims the promotion of research, as well as the democratization of access and dissemination of scientific information. It analyzes the relationship between access to the Portal and the indexed scientific production in the Web of Science (WoS) and Scopus databases, from 2013 to 2016, of the Federal Universities of Bahia, Ceará, Paraíba, Pernambuco and Rio Grande do Norte, because they are the five largest universities in the northeast region producing articles in the bases studied. Specifically, it seeks to map the access of these universities, as well as to characterize the scientific production, highlighting the Federal University of Paraiba in this context. To this end, it applies statistical techniques based on cientificometric indicators, with a quantitativequalitative approach, used to establish considerations about access to the Portal and the raise of scientific production. The methodological procedures are presented in phases: i) look up in the research instrument; ii) theoretical construction; iii) data collection at GEOCAPES databases, WoS and Scopus; iv) data processing; and v) interpretative analysis of the correlation between the data found. Thus, in view of the theoretical reference and the results, it concludes that in the regional scale there is no relation between access and scientific production, which occurs on a national scale. However, when considering the time required for the preparation and publication of the article, which occurs on average two years after the access to the databases, it is identified that there is a relationship between access and scientific production also on the regional scale. This implies, for example, that the access to the databases in 2013 will possibly have its scientific impact visualized in 2015, when new articles are published and the uses of journal citations are checked. The data show that the greatest access during the quadrennium was in the year 2014 and, in 2016, it was the one of greatest publication. In addition, it was verified that the scientific production of the IFES / NE are in rapid growth. Finally, it demonstrates alternatives for strengthening and targeting the Portal as a public policy to support scientific research in Post-graduate studies.